Hysterothylacium amoyense (Nematoda: Raphidascarididae) infecting Trichiurus lepturus (Scombriformes: Trichiuridae) from Demak, Central Java, Indonesia - Utami, Alusia Melanita Ria (Society for Indonesian Biodiversity, 2022)
Utami AMR, Murwantoko, Istiqomah I, Triyanto, Setyobudi E. 2022. Hysterothylacium amoyense (Nematoda: Raphidascarididae) infecting Trichiurus lepturus (Scombriformes: Trichiuridae) from Demak, Central Java, Indonesia. Biodiversitas 23: 1030-1037. This study aims to determine parasitic infection and identify the larvae of anisakid nematode found on the hairtail Trichiurus lepturus caught on the northern coast of Demak District, Central Java Province, Indonesia. One hundred seventy-eight hairtail samples were collected from fishermen who caught the fish at the Java Sea north coast of Demak. Fish specimens were measured (length) and weighed, then examined for anisakid larvae examination in the abdominal cavity, internal organs, and muscle. Data analysis included prevalence, mean intensity, and distribution of anisakid larvae on target organs. Selected samples of collected anisakid larvae were identified molecularly using PCR direct sequencing method. The results showed that the hairtail at the northern coast of Demak District was susceptible to anisakid larvae infection, on the category "frequently infected" with the prevalence of 56% and low mean intensity of infection of 2.43 larvae/host. Anisakid larvae were mainly found in the abdominal cavity (67%); followed by the digestive tract (19%), liver (13%), and gonads (1%). There were no anisakid larvae infecting the muscle tissue. Molecular analyses identified the anisakid infecting Trichiurus lepturus as Hysterothylacium amoyense.